Hydrogen Sulfide Attenuates Aortic Remodeling in Aortic Dissection Associating with Moderated Inflammation and Oxidative Stress through a NO-Dependent Pathway - Hsin-Ying Lu; Hung-Lung Hsu; Chih-Han Li; Shao-Jung Li; Shing-Jong Lin; Chun-Ming Shih; Chun-Che Shih (Antioxidants, 2021)
Aortic dissection (AD) is a highly lethal vascular disease characterized by separation of the constituent layers of the aortic wall. An increasing body of research indicates that inflammatory response and oxidative stress are implicated in vascular remodeling, which plays a key role in the development of AD. Hydrogen sulfide (H2S) has been found to protect against various types of cardiovascular disease, including myocardial infarction, arthrosclerosis, and hypertension. However, research on the effect of H2S on AD is insufficient. This study therefore elucidated the effect of H2S on the development and progression of AD, and the potential mechanism involved. Using β-aminopropionitrile fumarate (BAPN) and angiotensin II (Ang-II)-induced AD animal models, the administration of NaHS (as H2S donor, 56 μmol/kg body weight/day) was found to retard the development of AD. Murine VSMCs (Movas) exposed to interleukin-6 (IL-6) (20 ng/mL) to induce phenotypic switch. Histological analyses indicated that H2S administration inhibited the accumulation of inflammatory cells in the aortic wall and the related expression of inflammatory genes. Additionally, H2S treatment elevated aortic superoxide dismutase (SOD) activity and ablated malonaldehyde (MDA) and nitric oxide (NO) levels. In mechanistic terms, H2S attenuated IL-6 induced a pathological VSMC phenotypical switch through NO modulation by N(G)-monomethyl-L-arginine acetate salt (L-NMMA) stimulation. H2S inhibits AD formation by decreasing the inflammatory response, and oxidative stress, and by positively participating in vascular remodeling. These findings suggest a role for H2S as a novel and promising therapeutic strategy to prevent AD development.